Use of direct and indirect protocols in the assessment of maximal oxygen consumption - Schaurich, Mateus (2018)
Introduction: The concern with the development of the physical capacity linked to the cardiorespiratory resistance is emphasized in the physical training, being the maximal oxygen uptake one of the main functional parameters analyzed. Objective: verify if there is relation between the metods, as well as to define variation percentages of predictive equations of VO2max in an indirect way by submaximal and maximal tests compared to VO2max obtained through a direct way. Methods: The present cross-sectional study of correlational nature evaluated 50 male soccer players, aged 17-34. The subjects were submitted to ergoespirometric test and indirect methods. Results: In general, was found association between DP and IP on maximal (M) and submaximal (S) tests (M: r= 0,439; S: r=0,358), as well as by position, to left and right-backs (M: r=0,761; S: r=0,738) and forwards (M: r=0,778; S: r=0,733). Indirect assessments of maximal and submaximal tests did not present significant differences to DP, being observed a better relation of the maximal exercise tests protocol and the DP, when compared to the submaximal tests. Conclusion: The indirect evaluations, both through maximum and submaximal protocol, did not present significant differences in maximal oxygen uptake with the direct evaluation performed by ergospirometry.